Chloramphenicol – not so innocuous: a case of optic neuritis. (20th January 2011) - Fung, Adrian T; Hudson, Bernard; Billson, Frank A
Abstract : The authors present a case of optic neuritis in an adult patient who had been self-prescribing extraordinarily large dosages of chloramphenicol for chronic prostatitis over several years. The visual symptoms resolved upon cessation of the drug and prescription of B group vitamins. Chloramphenicol optic neuritis has not been described in the literature for over 20 years and previously predominantly in children with cystic fibrosis.